Application of the SAW Method for Recommendations for Determining Recruitment of Backend Engineers - Mellyza Rismawan; Muhamad Miftahudin; Rajib Ghaniy (Universitas Binaniaga Indonesia, 2023)
Determining the acceptance of candidate backend engineers will go through various stages and an assessment process based on certain predetermined criteria or requirements. However, the problem faced at this time is the result of an assessment that has almost the same score weight, close to the same or even exactly same, of course this will make it difficult for the manager concerned to make a decision. Therefore, the implementation of a Decision Support System (DSS) using the Simple Additive Weighting (SAW) method on this problem is one of the right and effective ways. The decision support system created in this study has successfully implemented the SAW method based on candidate backend engineer data which has been processed using 8 criteria, namely Golang, Test Results, Code Readability, Documentation, Unit Tests, Tech Experience, Design System, Code Scalability. And the ranking results have been tested using Spearman Rank correlation calculations and yielded a value of 0.98, which means that the SAW method can be used to determine recommendations for accepting backend engineer candidates